2022
DOI: 10.3390/textiles2030023
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Based Fuzzy Logic Method to Speculate Yarn Quality Ratio in Jute Spinning Industry

Abstract: Jute is a bio-degradable, agro-renewable, and widely available lingo cellulosic fiber having high tensile strength and initial modulus, moisture regain, good sound, and heat insulation properties. For these unique properties and eco-friendly nature of jute fibers, jute-based products are now widely used in many sectors such as packaging, home textiles, agro textiles, build textiles, and so forth. The diversified applications of jute products create an excellent opportunity to mitigate the negative environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…When the studies in the literature were examined, no study was found in which the temperature and time parameters and artificial intelligence programming method were used together in the drying process of yarn mixture ratios in knitted fabrics. The textile sector is one of the most developed sectors in Turkey and the detection of measurement results with artificial intelligence methods comes to the fore [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…When the studies in the literature were examined, no study was found in which the temperature and time parameters and artificial intelligence programming method were used together in the drying process of yarn mixture ratios in knitted fabrics. The textile sector is one of the most developed sectors in Turkey and the detection of measurement results with artificial intelligence methods comes to the fore [17,18].…”
Section: Introductionmentioning
confidence: 99%